SYNERGY OF ADVERTISING INFORMATIVENESS AND ADVERTISING PERSUASIVENESS ON BRAND AWARENESS AND PURCHASE DECISIONS FOR TOTO SANITARY PRODUCTS - John Tampil Purba; Laurensia Kelly (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
This study examines the impact of advertising informativeness, persuasiveness, product quality, price, and brand awareness on consumer purchase decisions for TOTO sanitary products. It also aims to explore brand awareness as a mediating factor influencing purchase decisions. Data were collected through an online survey via Google Forms, using a quantitative approach, with participants aged 18 to 60 years in the Jabodetabek area of Indonesia. The data were analysed using IBM SPSS Statistics version 27 and AMOS version 24, employing the Structural Equation Modelling (SEM) approach. The findings revealed that advertising informativeness, persuasiveness, product quality, and price significantly positively impact purchase decisions, supported by the mediating role of brand awareness. This study aims to enhance understanding of key marketing factors influencing purchase decisions and contribute valuable insights for future research.